2011
DOI: 10.1371/journal.pone.0020959
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility for Individual Cooperation Preferences: The Role of Monoamine Oxidase A Gene (MAOA) in the Voluntary Provision of Public Goods

Abstract: In the context of social dilemmas, previous research has shown that human cooperation is mainly based on the social norm of conditional cooperation. While in most cases individuals behave according to such a norm, deviant behavior is no exception. Recent research further suggests that heterogeneity in social behavior might be associated with varying genetic predispositions. In this study, we investigated the relationship between individuals' behavior in a public goods experiment and the promoter-region functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 63 publications
2
27
0
Order By: Relevance
“…Cesarini et al, 2009b) and genetic association designs (e.g., Knafo et al, 2008) Taken together, these results corroborate our previous findings (Mertins et al, 2011) using different elicitation procedures. In particular, by investigating behavior in a setting where there is no uncertainty, we ensure that behavioral differences do not stem from differences in expectations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Cesarini et al, 2009b) and genetic association designs (e.g., Knafo et al, 2008) Taken together, these results corroborate our previous findings (Mertins et al, 2011) using different elicitation procedures. In particular, by investigating behavior in a setting where there is no uncertainty, we ensure that behavioral differences do not stem from differences in expectations.…”
Section: Discussionsupporting
confidence: 91%
“…6 In particular, our previous findings (Mertins et al, 2011) suggested significant gender differences in the association between MAOA and cooperativeness. Those differences might be due to hormones such as testosterone and estrogen and their receptors, which act on gene regulation and subsequent brain development in a gender-specific manner (Hines, 2011;Kuo et al, 2010).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This division of people into distinct social types has been the accepted basis for new fields of research investigating the cultural, genetic, and neuronal bases of this variation (3)(4)(5)(6)(17)(18)(19)(20). Some studies have suggested these differences can be exploited by policies to make societies behave in a more public spirited way (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…10 The consequences of imputation have received scant attention, and this clearly generates measurement error, which is something that labor economists have a rich set of tools to offer to other researchers. 11 Specifically, Greiner and Rubin (2011) Knafo et al (2008), Mertins et al (2011), andZhong et al (2009) for studies that link specific genetic variants to outcomes measured in the laboratory. 14 Chabris et al (2012) discuss the importance and challenge of replicating results from studies using genetic data since this is needed to verify that the reported associations are not false positives.…”
Section: Discussionmentioning
confidence: 99%